2018
DOI: 10.1016/j.jcrs.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular microbypass stents as minimally invasive approach after conventional glaucoma filtration surgery

Abstract: For eyes with previous filtration surgery and medically uncontrolled IOP, the implantation of 2 stents provided a minimally invasive and safe reduction of mean IOP to less than 18 mm Hg at 12 months. The number of medications was also reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In the present cohort, IOP decreased by over 8 mmHg, a reduction of 37%; this reduction is approximately two to four times greater than the reduction expected with cataract surgery alone. This is consistent with clinical studies showing significantly greater reductions in IOP and medication use in patients with iStent and iStent inject implantation plus cataract surgery compared to cataract surgery alone [ 2 4 , 31 , 41 – 43 ]. It also aligns with the work of Fernandez-Barrientos et al [ 2 ], who demonstrated significant increases in trabecular outflow facility at 12 months in eyes implanted with iStent in combination with cataract surgery compared to eyes with cataract surgery alone.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present cohort, IOP decreased by over 8 mmHg, a reduction of 37%; this reduction is approximately two to four times greater than the reduction expected with cataract surgery alone. This is consistent with clinical studies showing significantly greater reductions in IOP and medication use in patients with iStent and iStent inject implantation plus cataract surgery compared to cataract surgery alone [ 2 4 , 31 , 41 – 43 ]. It also aligns with the work of Fernandez-Barrientos et al [ 2 ], who demonstrated significant increases in trabecular outflow facility at 12 months in eyes implanted with iStent in combination with cataract surgery compared to eyes with cataract surgery alone.…”
Section: Discussionsupporting
confidence: 88%
“…iStent inject implantation was completed following standard phacoemulsification and intraocular lens (IOL) implantation. As described previously [ 23 31 ], the iStent inject implantation technique may be summarized as follows: after pupillary miosis with a cholinergic agent (carbachol), the anterior chamber is filled with a medium-viscosity ocular viscosurgical device (OVD) and the surgeon then guides a single-use stainless steel injector through a temporal clear corneal incision in order to deliver two pre-loaded titanium stents ab interno into the nasal Schlemm’s canal approximately two clock-hours apart. Each heparin-coated 360 µm × 230 µm stent has multiple lateral outlet lumens for fluid outflow and a symmetric design facilitating implantation in either the right or the left eye (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have highlighted the efficacy of the iStent Inject with and without concomitant cataract surgery in reducing the IOP and medication burden [18][19][20][21][22][23][24][25][26][27]. In this study, we present a large consecutive case series of eyes undergoing iStent Inject implantation with concomitant cataract surgery by a single surgeon at an academic ophthalmology center in Montreal, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes support existing literature showing substantial reductions in medication after iStent and iStent inject implantation. [44][45][46] The iStent inject device is designed to have three general advantages over the iStent, as highlighted in a recent comparative study by Guedes et al 30 First, the iStent inject injector is pre-loaded with two stents (rather than one) in order to bypass two separate areas of the trabecular meshwork. Each stent is precisely designed to facilitate the needed flow of aqueous through the trabecular meshwork, which in a normal healthy eye averages 2.5 µL/ min.…”
Section: Discussionmentioning
confidence: 99%